Removal of triclosan from aqueous solution using biochar derived from seed shell of Aesculus turbinata - Cho, Eun Ji; Moon, Joon Kwan; Lee, Chang Gu; Park, Seong Jik (Desalination and Water Treatment, 2022)
The applicability of biochar derived from Aesculus turbinata seed shell (SAT-BC) was investigated for triclosan removal, which is extensively used in personal care products and causes endocrine dis-orders. The seed shells were pyrolyzed at 300°C–700°C, and their physico-chemical properties and triclosan adsorption capacities were analyzed. The increase in pyrolysis temperature from 300°C to 700°C decreased the O/C and H/C of SAT-BC from 0.205 to 0.130 and from 0.071 to 0.021, respec-tively. SAT-BC at 300°C (SAT-300) presented a higher triclosan adsorption capacity than that of SAT-BC pyrolyzed at other temperatures. Adsorption equilibrium was achieved at a reaction time of 6 h, and the pseudo-second-order model better fit the triclosan adsorption by SAT-300. The equilibrium adsorption data was best represented by the Freundlich isotherm model, and the maximum adsorption capacity was estimated to be 49.4 mg/g. The enthalpy and entropy change during triclosan adsorption by SAT-BC were 22.2 kJ/mol and 67.9 J/K·mol, respectively, indicating that the triclosan adsorption absorbed energy and increased the randomness during the processes. The increase of solution pH from 3 to 11 decreased triclosan adsorption from 33.0 to 7.4 mg/g, and a sharp drop in adsorption amount (23.5–14.6 mg/g) was observed between solutions pH 7 and 9. Increasing the SAT-300 dose from 1.7 to 10.0 g/L decreased the triclosan adsorption per unit mass of adsorbent, but increased the removal percentage; 8.3 g/L of the adsorbent dose removed more than 90% of triclosan. The biowaste turbinate seed shell pyrolyzed at 300°C can be potentially used for triclosan adsorption.
Keywords: Aesculus turbinata; Biochar; Elemental composition; Hydrogen bonding; Pyrolysis temperature; Triclosan